English Borrowings In Indonesian Print Media - Walean, Hanny A (JIU (Jurnal Ilmiah Unklab), 2000)
This study identified, described, and analyzed the structure, function and orthography of English Borrowing sin Indonesian Print Media. The data came from twenty-four essays taken from four periodicals and two daily newspapers from February to July 1999. The results were on the word level and nominal in function. It was also found that most of the English borrowings underwent changes in spelling when they got into Indonesian corpus.